Use you graphing calculator in the y equals button
Answer:
8
Step-by-step explanation:
(8*4)3=96
3*4=12
12*8=96
Factor the following:
10 y^2 - 35 y + 30
Factor 5 out of 10 y^2 - 35 y + 30:
5 (2 y^2 - 7 y + 6)
Factor the quadratic 2 y^2 - 7 y + 6.
The coefficient of y^2 is 2 and the constant term is 6.
The product of 2 and 6 is 12.
The factors of 12 which sum to -7 are -3 and -4. So 2 y^2 - 7 y + 6 = 2 y^2 - 4 y - 3 y + 6 = y (2 y - 3) - 2 (2 y - 3):
5 y (2 y - 3) - 2 (2 y - 3)
Factor 2 y - 3 from y (2 y - 3) - 2 (2 y - 3):
Answer: 5 (2 y - 3) (y - 2)
Any graph f(x) can be changed to f(x-3) by changing any x to x-3.
For example: Let f(x) = x^{2} + 2x + 4
Find f(x-3) by replacing all x's with x-3.
f(x-3) = (x - 3)^{2} + 2(x - 3) + 4
Then we can simplify and we will have f(x-3).